2012
DOI: 10.1039/c1em10521c
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the proximity effect for indoor air pollutant sources in two homes

Abstract: Personal exposure to air pollutants can be substantially higher in close proximity to an active source due to non-instantaneous mixing of emissions. The research presented in this paper quantifies this proximity effect for a non-buoyant source in 2 naturally ventilated homes in Northern California (CA), assessing its spatial and temporal variation and the influence of factors such as ventilation rate on its magnitude. To quantify how proximity to residential sources of indoor air pollutants affects human expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 20 publications
6
51
0
Order By: Relevance
“…The breathing zone of this person, who was 1.8 m (5 feet 10 inch) tall, was approximately 1.6 m above the sidewalk, whereas the sitting smoker's breathing zone was approximately 1 m above the sidewalk, and the greater height may explain the lower exposure of the standing person compared with the exposure of the nonsmokers on the bench. An experimental indoor air quality proximity study with an array of up to 37 CO monitors reported that the highest concentrations occurred at the same height as the source (Acevedo-Bolton et al, 2012), and a similar phenomenon could apply to smoking outdoors.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The breathing zone of this person, who was 1.8 m (5 feet 10 inch) tall, was approximately 1.6 m above the sidewalk, whereas the sitting smoker's breathing zone was approximately 1 m above the sidewalk, and the greater height may explain the lower exposure of the standing person compared with the exposure of the nonsmokers on the bench. An experimental indoor air quality proximity study with an array of up to 37 CO monitors reported that the highest concentrations occurred at the same height as the source (Acevedo-Bolton et al, 2012), and a similar phenomenon could apply to smoking outdoors.…”
Section: Resultsmentioning
confidence: 99%
“…The high concentrations and wide ranges can be attributed to the multiple microplumes reaching each person. Acevedo-Bolton et al (2012) reported a proximity study in which adjusting the exposure by subtracting a small quantity from each measurement improved the linearity of the distributional fit. The quantity they subtracted-obtained by using a trial-and-error approach maximizing R 2 -was very small.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations